Novel microwave-assisted solid dispersion technology enhances piroxicam dissolution and therapeutic efficacy: an in vitro and in vivo study - Kumar, Charit; Nanda, Arun (Creative Pharma Assent, 2025)
Background: Piroxicam (PRX), a nonsteroidal anti-inflammatory drug, exhibits poor aqueous solubility, limiting its therapeutic efficacy. Enhancing solubility can directly improve bioavailability and therapeutic effectiveness. This study explores the development of a new solid dispersion (SD) system of PRX using polyvinylpyrrolidone (PVP K30) as a carrier by MW-assisted method. Methods: The involvement of microwave (MW) in the solvent evaporation method is a newer concept aimed at enhancing the solubility and in vivo bioavailability of PRX. Various ratios of PRX: PVPK30 (1:5, 1:7, 1:9, and 1:11 w/w) were evaluated using conventional and MW-assisted solvent evaporation methods and conducted in vitro dissolution studies. Results: The optimized MW-assisted formulation (1:7 w/w) exhibited 94.69±0.24% drug release in 15 minutes, showing a 5.37-fold increase compared to pure PRX (17.63%) and surpassing the marketed drug release (90.82±0.39%). Fourier Transform Infrared, Differential Scanning Calorimetry, Thermogravimetric analysis, Scanning Electron Microscopy, and powdered X-ray diffraction authenticated the OF. In vivo studies demonstrated significant enhancements (p<0.0001) compared to control. The anti-inflammatory activity showed increased paw oedema inhibition (44.4±0.4%) compared to control and pure PRX (35.37±0.3%). The analgesic activity of OF demonstrated improved pain response time (10.6±0.8 seconds) compared to control (4.2±0.5 seconds) and pure PRX (8.1±0.7 seconds). Conclusion: The SD developed via the MW-assisted drug formulation technique significantly enhances the solubility, bioavailability, and therapeutic efficacy of PRX, offering a potential strategy to improve clinical outcomes for similar drugs with solubility challenges.